Maintenance of Customer Loyalty and Its Impact on Revenue: (A Case Study of Castle Hill Resort in Proctorsville, Vermont) - Dias Pebriana; Tanjung Prasetyo (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze customer loyalty maintenance strategies and their impact on revenue at Castle Hill Resort, Vermont. Using a descriptive qualitative approach, data were collected through in-depth interviews with hotel managers, internal documentation, and customer reviews. The findings reveal that loyal customers significantly contribute to direct bookings, visit frequency, and overall spending during their stays. Integrated loyalty strategies result in promotional cost efficiency and increased profit margins. Loyalty also serves as a strategic indicator with a direct effect on the hotel’s financial stability. Therefore, managing customer loyalty becomes a critical investment in sustaining and enhancing the competitiveness of independent hospitality businesses.